La peinture comme outil de connaissance de l’évolution du littoral : approche méthodologique - Edwige Motte (Cybergeo, 2019)
How and to what extent have coastal landscapes, natural environments and cultural heritage, been affected by both natural and anthropogenic influences over the last 200 years? While increasingly sophisticated technologies - satellite imagery, GPS surveys - now enable us to observe and monitor changing conditions within coastal zones, they do not provide the necessary perspective to understand phenomena that mainly - at least in Europe on the Channel coasts - date back to the Industrial Revolution. It is nevertheless possible, alongside these tools, to take advantage of the wisdom of hindsight by examining the vast additional resource of historical imagery. This paper introduces the methodology implemented to use coastal landscape artistic representations in order to increase the knowledge of coastal changes, through an exploratory approach carried out along the Brittany and Normandy shoreline.